2011
DOI: 10.1111/j.1364-3703.2011.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Species' identification and microarray‐based comparative genome analysis of Streptomyces species isolated from potato scab lesions in Norway

Abstract: Streptomyces strains were isolated from scab lesions on potatoes collected from different parts of Norway. Twenty-eight plant-pathogenic strains, as tested on seedlings of radish and on potato, were identified on the basis of physiological and molecular criteria. Polymerase chain reaction (PCR) analysis, using species-specific primers, and sequencing of the 16S rRNA gene identified 14 nonmelanin-producing strains to S. turgidiscabies. Fourteen melanin-producing strains were detected with primers specific to S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Such improvement is enabled by Soil DNA Isolation kits (MoBio Laboratories Inc., Solana Beach, CA) (Gonzalez-Franco et al 2009). Also, improvement of the use of specific primers and environmental clone libraries (McCaig et al 1999;Rintala et al 2001), DNA hybridization (Zaluga et al 2013), whole-genome microarray analysis (Dees et al 2012) and the 16S rRNA gene Microarrays PhyloChip technology (Weinert et al 2011) which proved to reveal more bacterial diversity in environmental samples than clone library (DeSantis et al 2007) will constitute a powerful approach for studying the Actinobacterial diversity. Still, a great development of the diversity knowledge could be the result of the great ongoing progress in their taxonomy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Such improvement is enabled by Soil DNA Isolation kits (MoBio Laboratories Inc., Solana Beach, CA) (Gonzalez-Franco et al 2009). Also, improvement of the use of specific primers and environmental clone libraries (McCaig et al 1999;Rintala et al 2001), DNA hybridization (Zaluga et al 2013), whole-genome microarray analysis (Dees et al 2012) and the 16S rRNA gene Microarrays PhyloChip technology (Weinert et al 2011) which proved to reveal more bacterial diversity in environmental samples than clone library (DeSantis et al 2007) will constitute a powerful approach for studying the Actinobacterial diversity. Still, a great development of the diversity knowledge could be the result of the great ongoing progress in their taxonomy.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, these authors concluded that ITS RFLP could be used as an alternative to the laborious DNA-DNA hybridization. This technique was used to assess diversity within populations of Actinobacteria (Song et al 2004b;Wanner 2009;de Leon et al 2009;Dees et al 2012). Many researches focused on the IGS between functional genes in Actinobacteria such as nif gene (Jamann et al 1993;Navarro et al 1997;Hahn et al 1999;Dai et al 2004).…”
Section: Genomic Fingerprinting Methodsmentioning
confidence: 99%
See 3 more Smart Citations